2021
DOI: 10.3390/info12110444
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Machine Learning & Natural Language Processing Techniques Applied for Predicting Depression Disorder from Online Support Forums: A Systematic Literature Review

Abstract: Depression is a common mental health disorder that affects an individual’s moods, thought processes and behaviours negatively, and disrupts one’s ability to function optimally. In most cases, people with depression try to hide their symptoms and refrain from obtaining professional help due to the stigma related to mental health. The digital footprint we all leave behind, particularly in online support forums, provides a window for clinicians to observe and assess such behaviour in order to make potential menta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 66 publications
0
11
0
1
Order By: Relevance
“…The deep learning module is an integral component of this process, which deftly interprets the user's language and actions to extract nuanced indications. The system can recognize indicators of stress, anxiety, depression, or other mental health conditions by examining patterns and changes over time [88]. The virtual psychological assistant can then provide customized help because it can forecast the user's mental state based on this analysis.…”
Section: Virtual Mental Health Assistantmentioning
confidence: 99%
“…The deep learning module is an integral component of this process, which deftly interprets the user's language and actions to extract nuanced indications. The system can recognize indicators of stress, anxiety, depression, or other mental health conditions by examining patterns and changes over time [88]. The virtual psychological assistant can then provide customized help because it can forecast the user's mental state based on this analysis.…”
Section: Virtual Mental Health Assistantmentioning
confidence: 99%
“…Recent text mining applications have allowed social scientists to observe natural online behaviour, gaining deeper insights into users’ real-time psychosocial characteristics [ 2 ]. Natural Language Processing (NLP), a subfield of Artificial Intelligence, is an emerging technology that uses machines to understand human languages [ 44 ]. The NLP process comprises the following steps: (a) text preprocessing, in which the dataset is cleaned by removing non-textual information (e.g., emojis, images, and HTML tags); (b) text representation, where the dataset is transformed into word vectors; (c) model training, during which algorithms are utilised to train a model (e.g., sentiment analysis, opinion mining, or topic modeling); and (d) model evaluation, where the model is evaluated to ensure it has optimal generalisability to other corpora [ 45 ].…”
Section: Mining Social Datamentioning
confidence: 99%
“…A statistical report says, all over the world almost 4.67 billion people are using the internet and searching for information for various reasons [15]. Many types of research are being done on depression detection.…”
Section: Introductionmentioning
confidence: 99%
“…Smith et al [19] interviewed 387 pregnant women and only 26% were screened for anxiety disorder. Arachchige et al [15] identified 1,335 references from different datasets and used ML and NLP for depression detection. They used Facebook, Twitter, and Reddit forums.…”
Section: Introductionmentioning
confidence: 99%